2020
DOI: 10.1055/a-1197-6534
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of endoscopic suturing to prevent adverse events and hospitalization after endoscopic submucosal dissection

Abstract: Background and study aim Endoscopic submucosal dissection (ESD) enables en bloc removal of gastrointestinal epithelial lesions but can leave a large mucosal defect, which can lead to inpatient observation and delayed bleeding or perforation. The aim of this study was to examine the safety and effectiveness of endoscopic suturing in closing ESD defects to prevent adverse events. Patients and methods In this single-center prospective cohort study, endoscopic suturing was performed to close ESD defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…In selective cases, closing a perforation can be achieved by pulling the omental fat into the gastric lumen and clipping the edges of the defect with the omental fat. 27,29 In a single center prospective cohort study involving 31 patients who underwent gastric (58.1 %) or rectal (41.9 %) ESD, Han et al 30 reported successful endosuturing in all patients with no instances of delayed bleeding or perforation.…”
Section: Management Of Gastric Perforationmentioning
confidence: 99%
“…In selective cases, closing a perforation can be achieved by pulling the omental fat into the gastric lumen and clipping the edges of the defect with the omental fat. 27,29 In a single center prospective cohort study involving 31 patients who underwent gastric (58.1 %) or rectal (41.9 %) ESD, Han et al 30 reported successful endosuturing in all patients with no instances of delayed bleeding or perforation.…”
Section: Management Of Gastric Perforationmentioning
confidence: 99%
“…The-Scope Clip (Ovesco Endoscopy) [11], endoscopic hand suturing [12], and the Overstitch system (Apollo Endosurgery) [13]. Most reports described prevention of post-ESD bleeding [8,[11][12][13]; however, E-LOC showed a higher sustained closure rate (95.8%) on POD 2-3 compared with other methods [10,12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Of the total, 54 proved potentially relevant for full-text review. Of these, 31 articles on the management of ESD-induced ulcers via endoscopic closure (hemoclips, endoclips, endoloop + endoclips, detachable snare + clips, OTSC + through-the-scope clips [TTSC], overstitch suturing, handsewn suturing) [31][32][33][34][35][36][37][38][39][40][41][42], tissue shielding methods (PGA sheets-based) [10,[43][44][45][46][47][48][49], and hemostatic powder/gel spray [18,19,[50][51][52][53][54][55][56][57][58], matched the selection criteria and were included in the systematic review. The key characteristics of each included study appear in Table 1.…”
Section: Identified Studies and Qualitymentioning
confidence: 99%